Information seeking in learning‐oriented search. Issue 1 (24th October 2017) - Ghosh, Souvick; Shah, Chirag
ABSTRACT: In this paper, we describe the different search behaviors exhibited by participants while performing learning‐oriented search tasks. The search tasks have been designed to represent the cognitive levels of learning hierarchically. We investigate how the searcher's behavior and perceived learning outcomes vary with increasing levels of cognitive complexity. In this study, we analyze the search log data of the participants, self‐reports, questionnaires and interviews both descriptively and statistically. Our results suggest that the perceived topic knowledge of the participants, perceived interest and difficulty assessments increase with increasing levels of the task. We use this study to discuss the preliminary results and highlight the limitations and future directions of this study.